2016
DOI: 10.1016/j.scitotenv.2016.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Influence on the oxidative potential of a heavy-duty engine particle emission due to selective catalytic reduction system and biodiesel blend

Abstract: Although the particulate matter (PM) emissions from biodiesel fuelled engines are acknowledged to be lower than those of fossil diesel, there is a concern on the impact of PM produced by biodiesel to human health. As the oxidative potential of PM has been suggested as trigger for adverse health effects, it was measured using the Electron Spin Resonance (OP(ESR)) technique. Additionally, Energy Dispersive X-ray Fluorescence Spectroscopy (EDXRF) was employed to determine elemental concentration, and Raman Spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 60 publications
(83 reference statements)
1
15
0
Order By: Relevance
“…In addition to the differences in size cuts, the variability between these studies is likely due to variability in waste grease feedstock, compared to biodiesel made from pure rapeseed oil or soybean oil. Other researchers have also attributed fuel source as an important contributing factor to the concentrations of specific metals like Cr, Cu, Mn in PM from biodiesel and diesel exhaust (Gangwar et al 2012;Godoi et al 2016). Gangwar et al (2012) found that B20 PM (biodiesel from karanja oil) contained higher concentrations of Fe, Mn, and Cr, whereas the Cu concentration in diesel PM was higher.…”
Section: Metals Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the differences in size cuts, the variability between these studies is likely due to variability in waste grease feedstock, compared to biodiesel made from pure rapeseed oil or soybean oil. Other researchers have also attributed fuel source as an important contributing factor to the concentrations of specific metals like Cr, Cu, Mn in PM from biodiesel and diesel exhaust (Gangwar et al 2012;Godoi et al 2016). Gangwar et al (2012) found that B20 PM (biodiesel from karanja oil) contained higher concentrations of Fe, Mn, and Cr, whereas the Cu concentration in diesel PM was higher.…”
Section: Metals Resultsmentioning
confidence: 99%
“…2013;Traviss et al 2014;Pourkhesalian et al 2015). Reactive metals and various organic species may influence the oxidative potential of PM (Cheung et al 2010;Charrier and Anastasio 2012;Fukagawa et al 2013;Fang et al 2015;Totlandsdal et al 2015;Godoi et al 2016); however, understanding the relationship between PM composition and health effects is a continued challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Grigoratos et al (2014) showed higher oxidative activity with increasing biodiesel blending when testing two light-duty vehicles with and without a DPF over the NEDC and Artemis cycles. Other studies have also demonstrated increases in oxidative activity with biodiesel blends (Cheung et al, 2009;Godoi et al, 2016;Guarieiro et al, 2014).…”
Section: Introductionmentioning
confidence: 89%
“…Finally, metals composition could also contribute to the negative health impacts associated with diesel and biodiesel PM. Previous studies show that metals, particularly transition metals such as Cu, are a major component of diesel and biodiesel PM (Betha and Balasubramanian, 2011;Traviss et al, 2014;Godoi et al, 2016). The presence of transition metals, and polar and nonpolar organic species in biodiesel and diesel PM can induce production of Reactive Oxygen Species (ROS) in vitro (Verma et al, 2010;Hemmingsen et al, 2011;Fukagawa et al, 2013;Godoi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies show that metals, particularly transition metals such as Cu, are a major component of diesel and biodiesel PM (Betha and Balasubramanian, 2011;Traviss et al, 2014;Godoi et al, 2016). The presence of transition metals, and polar and nonpolar organic species in biodiesel and diesel PM can induce production of Reactive Oxygen Species (ROS) in vitro (Verma et al, 2010;Hemmingsen et al, 2011;Fukagawa et al, 2013;Godoi et al, 2016). While ROS is integral to many cellular processes, increased exposure to ROS causes damage to intracellular components like DNA, lipids and proteins (Dröge, 2002).…”
Section: Introductionmentioning
confidence: 99%